Handbook of electrostatic processes - Chang, Jen-shih; Kelly, Arnold J.; Crowley, Joseph M. (Marcel Dekker, 1995)
Provides detailed, comprehensive descriptions of electrostatic processes as well as their applications in areas such as rheology, atomization and spraying, industrial dust particle precipitation and filtering, biomedical engineering, gas treatments, atmospheric electricity, chemical reactors, and electronic devices. Summarizes electrostatic fundamentals and electrical phenomena in solids and fluids.